Determinants of Leprosy Incidence in The Work Area of The Kebon Jeruk Health Center in 2019 - Rizky Aliyani Putri; Deasy Febriyanty (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Leprosy or leprosy is an infectious disease caused by infection with the bacterium Mycobacterium leprae (M. leprae) which attacks various parts of the body including nerves and skin. Based on data obtained from the Kebon Jeruk Health Center, leprosy cases were still found, namely from 2016 5 cases, then there was a very significant increase in 2017 to 16 cases, in 2018 to 14 cases, and 2019 until April 7 cases were found. This study aims to determine the factors related to the incidence of leprosy in the working area of ​​the Kebon Jeruk Public Health Center in 2019. This study used a case-control design with a sample size of 90 respondents. Sampling in this study used a simple random sampling technique for the case group and purposive sampling for the control group and analyzed with the chi-square test which was conducted from December 2019 to January 2020. In the results of this study, there were 30 respondents (33.3%) who suffered from leprosy. There is a significant relationship between age (ρ = 000), personal hygiene (ρ = 0.000) with the incidence of leprosy. It is recommended that respondents maintain personal hygiene and improve a clean and healthy lifestyle (PHBS).